A neuronal migratory pathway crossing from diencephalon to telencephalon populates amygdala nuclei. - García-Moreno, F; Pedraza, M; Giovannantonio, D; Di Salvio, M; López-Mascaraque, L; Simeone, A; De Carlos, J (2010)
Neurons usually migrate and differentiate in one particular encephalic vesicle. We identified a murine population of diencephalic neurons that colonized the telencephalic amygdaloid complex, migrating along a tangential route that crosses a boundary between developing brain vesicles. The diencephalic transcription factor OTP was necessary for this migratory behavior.